2020
DOI: 10.1093/ej/ueaa013
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Impact of Transportation Infrastructure

Abstract: Abstract There is a long-standing debate over whether new roads unavoidably lead to environmental damage, especially forest loss, but causal identification has been elusive. Using multiple causal identification strategies, we study the construction of new rural roads to over 100,000 villages and the upgrading of 10,000 kilometers of national highways in India. The new rural roads had precisely zero effect on local deforestation. In contrast, the highway upgrades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Researchers hypothesize that approximately 25 million km of new roads will be constructed by 2050 [196], with a large amount, potentially as high as 90%, being constructed in LMICs [15,191,198]. In many of these locations, roads will be constructed in some of the world's last remaining pristine wilderness areas, despite evidence that roads attract new forms of activity which directly impact land usage, forest cover, and particular species, and may contribute to larger-scale environmental degradation [9,15,191,192,195,196,198,201].…”
Section: Recommendation Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…Researchers hypothesize that approximately 25 million km of new roads will be constructed by 2050 [196], with a large amount, potentially as high as 90%, being constructed in LMICs [15,191,198]. In many of these locations, roads will be constructed in some of the world's last remaining pristine wilderness areas, despite evidence that roads attract new forms of activity which directly impact land usage, forest cover, and particular species, and may contribute to larger-scale environmental degradation [9,15,191,192,195,196,198,201].…”
Section: Recommendation Evidencementioning
confidence: 99%
“…Researchers hypothesize that approximately 25 million km of new roads will be constructed by 2050 [196], with a large amount, potentially as high as 90%, being constructed in LMICs [15,191,198]. In many of these locations, roads will be constructed in some of the world's last remaining pristine wilderness areas, despite evidence that roads attract new forms of activity which directly impact land usage, forest cover, and particular species, and may contribute to larger-scale environmental degradation [9,15,191,192,195,196,198,201]. Accordingly, new evidence suggests moving away from reactive approaches to environmental damage limitation [201] and supporting conservative and proactive enforcement strategies that minimize irreversible effects without prohibitively expensive postconstruction modifications [191,195,196].…”
Section: Recommendation Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…With the expansion of transportation infrastructure, the influence of human activities expands. For example, Asher et al discussed the impact of country road facilities construction on the forest ecological environment, and the results showed that the facility construction has no direct impact on forest quality, but the upgrading of roads has caused changes in ecological corridors, which have led to adverse environmental impacts [24]. The continuous expansion of human activities puts tremendous pressure on the ecological environment within the radiation range of transportation infrastructure.…”
Section: Introductionmentioning
confidence: 99%